2018
DOI: 10.1097/wco.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

Emerging antisense oligonucleotide and viral therapies for amyotrophic lateral sclerosis

Abstract: Advances in preclinical and clinical studies of ASO and viral directed approaches to neuromuscular disease, particularly ALS, indicate that these approaches have high specificity and are relatively well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 53 publications
(46 reference statements)
0
43
0
Order By: Relevance
“…However, efforts to optimize their potential clinical benefit are constrained by limited data describing normal, SMA disease baseline or present dosage regimen-achieved drug-induced SMN transcript and protein levels in the CNS, which cannot be assessed in living patients. The data reported here have important implications for optimization of therapeutics for SMA patients, but also highlight the importance of implementing such expedited autopsy programs to collect high-quality human CNS tissues in patients with other neurological diseases being targeted with novel gene targeting therapeutics (34,35).…”
Section: Discussionmentioning
confidence: 86%
“…However, efforts to optimize their potential clinical benefit are constrained by limited data describing normal, SMA disease baseline or present dosage regimen-achieved drug-induced SMN transcript and protein levels in the CNS, which cannot be assessed in living patients. The data reported here have important implications for optimization of therapeutics for SMA patients, but also highlight the importance of implementing such expedited autopsy programs to collect high-quality human CNS tissues in patients with other neurological diseases being targeted with novel gene targeting therapeutics (34,35).…”
Section: Discussionmentioning
confidence: 86%
“…Expansion of this repeat to hundreds or thousands of repeated segments is a recognized cause of fALS, frontotemporal dementia, and occasionally also sALS (Mis et al, 2017). The DNA encoding this repeat is transcribed bi-directionally, resulting in nuclear RNA inclusions, and is thought to promote gain of function toxicity (Ly and Miller, 2018;Staats et al, 2019). Other potential mechanisms include C9orf72 loss of function (Shi et al, 2018;Staats et al, 2019), or proteotoxicity (Gitler and Tsuiji, 2016).…”
Section: Structural Variants In Alsmentioning
confidence: 99%
“…One of the current strategies employed in the development of therapeutics for C9orf72 is to target the SV region with antisense oligonucleotides to induce transcript degradation by RNase H enzymatic cleavage, preventing the build-up of toxic C9orf72 transcript and protein. Other strategies focus on modulating the expression of transcription factors specifically involved in transcribing expanded repeats (Ly and Miller, 2018). Recently, it was shown that small ribosomal subunit protein (RPS25) plays a direct role in RAN translation, and decreasing its levels through RNA interface mediated reduction prolonged the lifespan of Drosophila with the expanded repeat (Yamada et al, 2019).…”
Section: Structural Variants In Alsmentioning
confidence: 99%
“…Hence, repeated tests of the same mouse is feasible, which enables longitudinal studies of drug efficacy with a powerful statistical design in which individual subjects are compared to themselves over time. Therapies that target patients with mutations of the SOD1 gene have successfully completed early clinical study phases, and have prolonged survival in SOD1 related animal models 27,28 . Microendoscopy measurements in animal models given these drugs should be performed to understand the effects of the drug on motor unit distribution over time in individuals, and further validate the measurement method.…”
Section: Scientific Reports |mentioning
confidence: 99%